Malignant features of Meningioma CT scan Study. - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2010)
CT scan features of Malignant MeningiomaObjective: Meningioma which is a common benign Brain tumor can be malignant, but the final decision is by biopsy. However CT. Scan features can help to evaluate malignancy of a lesion.The aim of this retrospective study is to look for the malignant features of a malignant meningioma .Patients and Methods: This is a retrospective study of 50 malignant meningiomas in the neurosurgical unit in the specialized surgical hospital (previously AL-Shaheed Adnan hospital), for the period from March 1992 to March 2007. We search specially for Malignant features on the CT scan study of the patients.Results: 94%of the patients had different features of malignant meningioma, only 6% CT scan did not show any malignant features, we also evaluated the results of surgery .Conclusion: CT scan is one of the most important diagnostic procedures for diagnosis of brain tumor; however final diagnosis can only be emphasized by the histo-pathological studies.